An Analysis of Compliance Level of Health Protocol Implementation at the Population Control and Family Agency in Central Sulawesi During the Covid-19 Pandemic - Adriana Saehana; Abdul Kadri; Sudirman Sudirman (Universitas Muhammadiyah Palu, 2021)
The purpose of the research is to determine the level of employees’ compliance with the implementation of health protocols at the Population Control and Family Planning Agency (P2KB) of Central Sulawesi during the COVID-19 Pandemic. This is qualitative research with the triangulation technique, which allows researchers to understand the role of each individual, policy, the authority of each personnel, obstacles faced by employees in carrying out their duties, and motivations that support the implementation of health protocols. The number of informants is four people using observation to determine compliance in the application of health protocols. The result indicates that knowledge of health protocols is very good. The employees have very high motivation in implementing health protocols and perceptions of serious threats if not implementing health protocols. It is expected that the institutions maximize the implementation of health protocol rules, provide sanctions for those who violate health protocols in carrying out daily work during the covid-19 Pandemic, and it is hoped that further research will be carried out with new variables so that research on the implementation of health protocols is expected. Can develop more.